مدى مشروعية العمل الطبي في الحالات غير العلاجية - الحراكي أحمد; المرعي أرديني (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يتناول هذا البحث مدى مشروعية العمل الطبي في بعض الحالات غير العلاجية، مثل رتق العذرية، وتغيير الجنس، واستئجار الرحم في إطار الإنجاب المساعد طبياً، والجراحة التجميلية، والتجارب والبحوث العلمية، والتعقيم الطبي. والأصل أن العمل الطبي لا يعد مشروعاً في الحالات السابقة، لأنه لا يهدف بحسب الأصل إلى العلاج والشفاء، غير أنه من الممكن أن يكون العمل الطبي في الحالات السابقة مشروعاً إذا كانت الغاية علاجية كاستثناء. وتوصل البحث إلى بعض النتائج والمقترحات التي يمكن أن تسهم في إصدار النصوص القانونية اللازمة من قبل المشرع الوطني. This research deals with Legitimacy extent of medical work in non-therapeutic cases such as virgin patching, sex change, medical sterility, lease of uterus for reproduction with medical assistance, plastic surgery and scientific research and experiments. The medical work is not legitimate in the previous cases, because it does not originally aim for therapy and cure, but it is possible that the medical work in the previous cases is legitimate if it is exceptionally aiming for therapy. The research concluded some results and recommendation, which may contribute in issuing required legal texts by the national legislator.